Transcutaneous Spinal Cord Stimulation Enhances Walking Performance and Reduces Spasticity in Individuals with Multiple Sclerosis - Ursula S. Hofstoetter; Brigitta Freundl; Peter Lackner; Heinrich Binder (Brain Sciences, 2021)
Gait dysfunction and spasticity are common debilitating consequences of multiple sclerosis (MS). Improvements of these motor impairments by lumbar transcutaneous spinal cord stimulation (tSCS) have been demonstrated in spinal cord injury. Here, we explored for the first time the motor effects of lumbar tSCS applied at 50 Hz for 30 min in 16 individuals with MS and investigated their temporal persistence post-intervention. We used a comprehensive protocol assessing walking ability, different presentations of spasticity, standing ability, manual dexterity, and trunk control. Walking ability, including walking speed and endurance, was significantly improved for two hours beyond the intervention and returned to baseline after 24 h. Muscle spasms, clonus duration, and exaggerated stretch reflexes were reduced for two hours, and clinically assessed lower-extremity muscle hypertonia remained at improved levels for 24 h post-intervention. Further, postural sway during normal standing with eyes open was decreased for two hours. No changes were detected in manual dexterity and trunk control. Our results suggest that transcutaneous lumbar SCS can serve as a clinically accessible method without known side effects that holds the potential for substantial clinical benefit across the disability spectrum of MS.